Anti-Inflammatory Salidroside Delivery from Chitin Hydrogels for NIR-II Image-Guided Therapy of Atopic Dermatitis - Shengnan He; Fang Xie; Wuyue Su; Haibin Luo; Deliang Chen; Jie Cai; Xuechuan Hong (Journal of Functional Biomaterials, 2023)
Atopic dermatitis (AD) is the most common heterogeneous skin disease. Currently, effective primary prevention approaches that hamper the occurrence of mild to moderate AD have not been reported. In this work, the quaternized β-chitin dextran (QCOD) hydrogel was adopted as a topical carrier system for topical and transdermal delivery of salidroside for the first time. The cumulative release value of salidroside reached ~82% after 72 h at pH 7.4, while in vitro drug release experiments proved that QCOD@Sal (QCOD@Salidroside) has a good, sustained release effect, and the effect of QCOD@Sal on atopic dermatitis mice was further investigated. QCOD@Sal could promote skin repair or AD by modulating inflammatory factors TNF-α and IL-6 without skin irritation. The present study also evaluated NIR-II image-guided therapy (NIR-II, 1000–1700 nm) of AD using QCOD@Sal. The treatment process of AD was monitored in real-time, and the extent of skin lesions and immune factors were correlated with the NIR-II fluorescence signals. These attractive results provide a new perspective for designing NIR-II probes for NIR-II imaging and image-guided therapy with QCOD@Sal.